A historical review of the evolution of nasal lavage systems. Issue 2 (10th February 2021) - Fandino, A; Douglas, R
Abstract: Background: Nasal lavage is an ancient practice that still has a fundamental role in the management of sinonasal conditions. The history related to these devices is extensive and remarkable. By reviewing it, it is hoped that a broader view can be achieved on what is currently possible with nasal lavage and how advances may be made in the future. Methods: A careful review of different sources, such as ancient manuscripts, registered patents and scientific papers, was conducted to achieve a thorough examination of the history related to nasal rinsing devices. Conclusion: Nasal lavage has evolved significantly since first considered for medical use and has always played a central role in the treatment of patients with sinonasal conditions. Further innovation is still necessary to surmount the shortcomings of current nasal lavage systems.